MAKHRAJ PENGUCAPAN HURUF HIJAIYAH DALAM BENTUK SIMULASI MODEL TABUNG VOCAL TRACT DARI ALAT UCAP MANUSIA - Muhammad Subali; Djasiodi Djasri; Neneng Alawiyah (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2014)
When reading the Qur'an, each letter should be pronounced according to its proper articulation (Makhraj). Mistake in pronunciation of a letter or makhraj can change the meaning of that letter. Elements of sound in Arabic is very important to learn in order to the pronunciation of the Arabic language accordance with the rules of the Arabic language that have been assigned. The purpose of this research is to analyze the pattern of frequencies called formant for each pronunciation hijaiyah which express the proper pronunciation. Data is obtained by recording the expert qori and qoriah, then processed with software ''Praat